Passagens da memória: ensaio biográfico sobre a artista Lysia de Araújo - Heleniara Amorim Moura (2015)
This work is a biographical essay about the actress and writer Maria Lysia Correa de Araujo (1921-2012) who produced a diverse literature, presenting a set of literary composition (in a variety of) genres such as theater critics, chronic, novel and short stories. This artist was often inserted in the (critical) aesthetics called fantastic realism or magical realism and her production is part of the Brazilian disturbed postmodernism context from the 50s, 60s and 70s XX century, at this moment it brings out a production close to the next generation of Spanish American literature in the country, which is contemporary, written surrounded by authoritarian and violent governments. Furthermore, as an actress, she was present at expressive art assemblies and the School of Dramatic Art of São Paulo awarded her. In her artistic life, she lived for a short time in various cities like São Paulo, Rio de Janeiro, Recife and Belo Horizonte participating in important theater groups such as Arena, Oficina, Cia Maria Della Costa, Cia Tônia Autran, among others. She worked with directors like José Celso Martinez, Augusto Boal, Alfredo Mesquita, while enacting pieces of deep ideological content in a period of silence and repression. Through a methodology straddles the concept of Benjamin in 'Passagen-werk', the faces of the fragment, quote, the remains, finally, a whole range of residual invests biographical material to the possibility of formation of a life story. From this set, we intend to conduct a biographical essay that can encompass multiple facets of the artist's existence, also extending it to a heterobiography memory, which allows us to understand the biographical spaces in which it takes the existence of Lysia de Araújo, her art and her writing